2021
DOI: 10.1007/s11164-021-04541-4
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network modeling of the hexavalent uranium sorption onto chemically activated bentonite

Abstract: This study aims to study the hexavalent uranium U(VI) adsorption onto chemically activated Algerian bentonite BMP-Na in order to guarantee a clean and environmentally friendly method of the elimination of waste in nuclear energy applications. The activation of the bentonite was done chemically using hydrochloric acid HCl and saturated with Na + cations using NaCl solution. The obtained bentonite has been characterized by using various methods such as XRD, SEM-EDX, FTIR, XRF and BET. Those characterizations hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Conventional physical and biological techniques, such as adsorption, reverse osmosis, and air stripping, can only extract soluble organic materials [11][12][13]. In actuality, they do not completely eliminate pollutants, they rather transfer them from one phase to another [14]. In general, these techniques have considerable drawbacks and disadvantages, one of which is contamination with treatment by-products, which can increase the risk of cancer and pollute the environment [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional physical and biological techniques, such as adsorption, reverse osmosis, and air stripping, can only extract soluble organic materials [11][12][13]. In actuality, they do not completely eliminate pollutants, they rather transfer them from one phase to another [14]. In general, these techniques have considerable drawbacks and disadvantages, one of which is contamination with treatment by-products, which can increase the risk of cancer and pollute the environment [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Organic contaminants and inorganic heavy metals are the most common substances that can cause harmful water pollution [4][5][6][7]. No matter how small the concentration of these pollutants in water may be, the organs of living beings might be damaged by long-term exposure to them [8,9]. Companies, such as pharmaceutical, textile, and thinner and metallurgical industries, are the primary sources of these water pollutants [10].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional methods of water treatment cannot effectively eliminate pollutants from wastewaters and could cause great harm to the environment [1][2][3][4]. On the other hand, it has been shown that photocatalysis is a promising approach for the degradation of nonbiodegradable compounds in water [5,6].…”
Section: Introductionmentioning
confidence: 99%